PENGARUH SENAM TRILOKA TERHADAP TINGKAT KECEMASAN LANSIA DI GRIYA LANSIA HUSNUL KHATIMAH - Tri Maghfuroh, Putri Nadzifatun; Marupa, Winda Rahmawati; Yuliadarwati, Nungki Marlian; Prastowo, Bayu (Jurnal Kesehatan Holistic, 2024)
Abstract Introduction : The elderly experience a phase of old age, which is characterized by physiological decline caused by biological aging, disease, and lifestyle, including anxiety. Triloka exercise is a low-intensity aerobic exercise performed in 16 sessions over three weeks which has a relaxing impact and reduces anxiety levels. Objective : To analyze the effects of Triloka excercise on the anxiety levels in the elderly at the Husnul Khatimah Home for the Elderly. Method : A pre-experimental method and a one-group pre-post test design procedure were applied in this study. A total of 32 respondents were recruited using a purposive sampling . Respondent's anxiety levels were measured before and after doing the Triloka exercise using the Hamilton Anxiety Rating Scale (HARS) measuring instrument. The research hypothesis was tested using the Wilcoxon signed rank test with the SPSS application. Results : Before Triloka exercise, mild anxiety dominated in as many as 15 people (47%), moderate anxiety as many as 14 people (44%), severe anxiety as many as 2 people (6%), and very severe anxiety in as many as 1 person (3%). Meanwhile, after receiving the Triloka exercise intervention, 21 respondents (67%) reported no anxiety, 8 reported mild anxiety (24%), and 3 reported moderate anxiety (8%). The data analysis test found that the p-value was 0.000<0.05 and that Triloka exercise had an effect on the anxiety level of the elderly at Home for the Elderly Husnul Khatimah. Conclusion : As a result, Triloka Excercise can be used to relieve anxiety in the elderly. Keywords: Aerobic Low Impact, Anxiety, Elderly,Triloka Exercise.